Occurrence of heavy precipitation influenced by solar wind high-speed streams through vertical atmospheric coupling - Prikryl, Paul; Rušin, Vojto (Frontiers in Astronomy and Space Sciences, 2023)
A tendency of heavy-rainfall-induced floods in Canada to follow arrivals of solar wind high-speed streams (HSSs) from coronal holes is observed. Cool season precipitation events, including extreme freezing rain events in the province of New Brunswick, also tend to occur following HSSs. More direct evidence is provided using the satellite-based gridded precipitation data set IMERG in the superposed epoch analysis of high-rate precipitation. The results show an increase in the high-rate daily precipitation occurrence over Canada following arrivals of major HSSs. This is consistent with previously published results for other mid-latitude geographic regions. The ERA5 meteorological reanalysis is used to evaluate slantwise convective available potential energy (SCAPE) that is of importance in the development of storms. The role of the solar wind-magnetosphere-ionosphereatmosphere coupling, mediated by globally propagating aurorally excited atmospheric gravity waves releasing the conditional symmetric instability in the troposphere leading to convection and precipitation, is proposed. Extreme weather events, such as heavy precipitation leading to floods or flash floods particularly in summer, and snow-or ice-storms in winter, pose natural hazards with major socio-economic and environmental consequences (Brooks et al., 2001;Buttle et al. 2016). Despite advances made in forecasting and improved understanding of mesoscale processes (Doswell and Bosart 2001), predictions of extreme precipitation events continue to present difficult challenges (Doswell and Bosart 2001;Villarini et al. 2010;Gourley et al. 2012). Such events are common in Canada and with the climate change affecting the stability of Earth's atmosphere their occurrence is expected to increase (Burn and Whitfield 2016). Buttle et al. (2016; their Table 2) reviewed the key processes, classified as meteorological, hydrological, geomorphic and human induced, that generate floods in Canada.In this paper we focus on heavy precipitation events in Canada where the proximity of the auroral zone, the source region of atmospheric gravity waves (AGWs), makes it the most favorable geographic location to investigate the relationship between high-rate precipitation occurrence and solar wind high-speed streams.